2010
DOI: 10.1242/dmm.002634
|View full text |Cite
|
Sign up to set email alerts
|

Involucrin–claudin-6 tail deletion mutant (CΔ206) transgenic mice: a model of delayed epidermal permeability barrier formation and repair

Abstract: SUMMARY Preterm birth is a major global health problem that results in a large number of infant deaths, many of which are attributable to the complications of an immature epidermal permeability barrier (EPB), for which there is currently no effective therapeutic option. The mammalian EPB is formed during development and is essential for survival as it maintains thermoregulation and hydration, and provides a defense against infection. Using transgenic mouse technology, we have demonstrated the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…7 Studies using the other claudin-6 mutated transgenic mouse also highlighted the importance of specific claudins' characteristics to in vivo phenotype. 8,9 However, even in the epidermis, how claudin orchestrates its many effects is poorly understood. Recently, the crystal structures of claudin-4, -15, and -19 were reported; these studies suggested the structural basis for the molecules that create the TJ paracellular barriers and channels, and other claudin functions.…”
Section: Tight Junction and Claudinsmentioning
confidence: 99%
“…7 Studies using the other claudin-6 mutated transgenic mouse also highlighted the importance of specific claudins' characteristics to in vivo phenotype. 8,9 However, even in the epidermis, how claudin orchestrates its many effects is poorly understood. Recently, the crystal structures of claudin-4, -15, and -19 were reported; these studies suggested the structural basis for the molecules that create the TJ paracellular barriers and channels, and other claudin functions.…”
Section: Tight Junction and Claudinsmentioning
confidence: 99%
“…Another group of investigators also reported that SBSN deficiency is one of the factors related to AD pathogenesis 4 . Similarly to knockout mice for the other epidermal differentiationassociated proteins [24][25][26][27] , Sbsn -/mice were viable and healthy, without apparent growth restriction. Sbsn -/mice did not show any of the crucial features of typical (extrinsic) AD, including skin barrier dysfunction and high transcutaneous responses.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm birth is a major global health problem that causes a large number of infant deaths, many of which can be attributed to complications of immature EPB [42]. An integral EPB in premature birth is crucial for maintaining temperature stability, preventing microbial infection through the skin.…”
Section: The Epidermal Permeability Barrier (Epb)mentioning
confidence: 99%
“…The skin of 2-week-old mice overexpressing a shorter deletion in the cytoplasmic tail domain of Cldn6 (Inv-Cldn6-C∆196) have striking histological abnormalities compared with the wild-type, as evidenced by epidermal hyperplasia and hyperkeratosis, which is similar to the skin of Inv-Cldn6 and Inv-Cldn6-C∆187 mice [45]. Mice expressing Cldn6 with a shorter tail deletion (Inv-Cldn6-C∆206) possess a distinct developmental defect in epidermal differentiation resulting in EPB formation delays [42]. The above mutants of CLDN6 lead to its cytoplasmic localization while affecting the expression and localization of other CLDNs, such as CLDN5, 8, 10, 11, 12, and 18, emphasizing the importance of the CLDN6 tail domain for membrane targeting and suggesting that the CLDN6 tail domain is essential for CLDNs homeostasis and EPB formation.…”
Section: The Epidermal Permeability Barrier (Epb)mentioning
confidence: 99%